Mentha piperita extract as a natural product for the corrosion inhibition of low carbon steel in a polluted NaCl environment: Chemical, electrochemical and biological studies (Indian Journal of Chemical Technology (IJCT), 2023)
The impact of aqueous Mentha piperita extract (MPE) as a corrosion inhibitor for low carbon steel (LCS) in NaCl/Na2S solution has been investigated using chemical and electrochemical techniques to evaluate the protection performance of MPE. ―As the concentration of the extract increased, the protection efficiency (PE) increased, reaching 91.2% at 300 ppm, whereas the increase in temperature favoured to slow decrease‖.The extract has been physically adsorbed on the metal surface according to the Temkin isotherm. Polarization data reveal that this extract acts as a mixed inhibitor. The mechanism of corrosion protection of MPE has been discussed from electrochemical techniques. MPE has been adsorbed on LCS obeying Temkin isotherm. Surface morphology techniques such as scanning electron microscopy (SEM) and atomic force microscopy have been used to demonstrate the creation of a protective coating on the LCS in the presence of MPE. The extract inhibits the bacterial activity of Escherichia coli.